Back Cover: Potent Trivalent Inhibitors of Thrombin through Hybridization of Salivary Sulfopeptides from Hematophagous Arthropods (Angew. Chem. Int. Ed. 10/2021). Issue 10 (4th February 2021) - Agten, Stijn M.; Watson, Emma E.; Ripoll‐Rozada, Jorge; Dowman, Luke J.; Wu, Mike C. L.; Alwis, Imala; Jackson, Shaun P.; Pereira, Pedro José Barbosa; Payne, Richard J.
Abstract : A novel class of trivalent thrombin inhibitor is reported by Pedro José Barbosa Pereira, Richard J. Payne, and co‐workers in their Research Article on page 5348 . These inhibitors were rationally designed by hybridizing native sulfopeptide thrombin inhibitors from three different invertebrates: variegin from a bont tick, anophelin from the Anopheles mosquito, and TTI from the tsetse fly. When fused using bidirectional peptide synthesis and peptide ligation technologies the resulting hybrid inhibitors exhibited exquisite potency both in vitro, with femtomolar inhibition constants, and in an in vivo model of thrombosis.